Neurodevelopmental Outcomes in Infants with Retinopathy of Prematurity and Bevacizumab Treatment. - Reyin Lien; Mu-Hsien Yu; Kuang-Hung Hsu; Pei-Ju Liao; Yen-Po Chen; Chi-Chun Lai; Wei-Chi Wu (PLoS ONE, 2016)
The current study aims to investigate the neurodevelopment of premature infants after intravitreal injections of bevacizumab (IVB) for the treatment of retinopathy of prematurity (ROP) up to the age of 2 years.The study design was retrospective observational case series conducted at an institutional referral center. Infants with type 1 ROP were classified into 3 groups: laser only, IVB only, and a combination of IVB and laser treatment. Main Outcome Measures were neurodevelopmental outcomes of the patients after treatment were assessed by Bayley Scales for Infant Development.Sixty-one patients who finished the neurodevelopmental survey were included. No detrimental effects on neurodevelopment were found in IVB group compared with the patients who received laser treatment only. The patients in the IVB + laser group had a higher incidence of significant mental (p = 0.028) and psychomotor (p = 0.002) impairment at 24 months than the patients in the laser group. The odds ratio of having severe psychomotor defects in the IVB + laser group was 5.3 compared with the laser group (p = 0.041). The causal source for the differences that were detected remained unknown due to lack of randomization in the study and accompanying bias in patient selection.Two years after laser and/or intravitreal injections of bevacizumab for infants with retinopathy of prematurity, no difference on neurodevelopment for those who received only bevacizumab versus only laser treatment were found. Those infants who required rescue therapy with laser or bevacizumab injection after initial, unsuccessful treatment showed some detrimental, neurodevelopmental effects.